Analisis Pengaruh Total Assets Turnover, Debt To Assets Ratio, Debt To Equity Ratio, Dan Return On Equity Terhadap Return On Assets Pada E-Commerce 2020-2022 - Andaradanta, Davin Dawa; Iradianty, Aldilla (eProceedings of Management, 2024)
a